Analysis of Students’ Ability to Rearrange Jumbled Sentences into an Effective Procedure Text - Feby, Feby (Lentera : Jurnal Kajian Bidang Pendidikan dan Pembelajaran, 2023)
An explanation of how something is accomplished through a series of steps or actions is given in a procedure text. It has features of language, general structure, and text arrangement. The goal of this study was to find out whether or not students could successfully rearrange a collection of sentences into a process text. Descriptive research methodology was used. Students of vocational high school Kartika 1-2 Padang's second year made up the study's population. Forty students made up the samples. Utilizing proportional stratified random sampling, the sample was taken. The researcher used a writing test instrument called a scrambled sentence test to get the data for this study. According to the results, it can be said that the second-year students at vocational high school Kartika 1-2 Padang had a fair amount of aptitude for organizing sentences into an effective procedural text. Therefore, the teacher should go over the process text materials and encourage the pupils to learn more about procedure text.